Market Basket Analysis of Customer Buying Patterns at Corm Café - Isa, N.; A.Kamaruzzaman, N.; A. Ramlan, M.; Mohamed, N.; Puteh, M. (International Journal of Engineering and Technology, 2018)
Market Basket Analysis (MBA) is a technique in data mining used to seek the co-occurrence set of items in a large dataset or database. It is usually used in mining transactions or basket data, especially in retail. This technique has been proven beneficial in understanding customer buying patterns and preferences. It has been widely used in multinational companies. Current business trends have changed dramatically, parallel with the advancement of technology. Changes in customer demand requires an improvement in accuracy of business operations. This paper proposes the implementation of MBA at a Small Medium Enterprise business, a case study at Corm Café. Daily transaction data taken from customer order sheets has been used. A detailed implementation is demonstrated in the paper. The results identify a trend in customer buying patterns, which is useful information for the owner in planning their business operation.